Studi Minat Masyarakat terhadap Bank Syariah dan Bank Konvensional di Kampung Sumadra - Agustiana, Rian; Effendi, Pranoto; Setiawan, Azis Budi (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2025)
This research aims to analyze the comparison of public interest in Sharia Banks and Conventional Banks in Sumadra Village, Garut Regency, using qualitative methods through interviews with twelve respondents. The analysis results show that the main factors in bank selection involve business needs, income level, and ease of access. Conventional banking practices that are sustainable in the local environment are the main selection factor. Ease of use of banking services, especially transfers and savings and loans, is also a key consideration. Although awareness about Islamic banking exists, not all respondents seek further information about Islamic banking services. However, the majority showed positive interest in Islamic banking, with a desire to use such services if they were more accessible. The obstacles faced by Islamic banks are limitations and lack of service networks. Therefore, it is recommended that Islamic banks consider expanding service networks and improving marketing strategies.